Effects of activated carbon on liquefaction resistance of calcareous sand treated with microbially induced calcium carbonate precipitation. Issue 161 (October 2022) - Shan, Yi; Zhao, Jitong; Tong, Huawei; Yuan, Jie; Lei, Donglin; Li, Yuanyuan
Abstract: Microbially induced calcium carbonate precipitation (MICP) is a new, natural, environmentally friendly treatment method for soil foundations, which can improve the resistance of calcareous sand foundations to liquefaction. Liquefaction is prone to occur under dynamic loading caused by events such as earthquakes or sea waves. Activated carbon is a porous substance that also offers the property of adsorption. In this study, the adsorption capacity of activated carbon was used to improve the retention ratio of bacteria during MICP treatment. Bacterial retention tests, cyclic triaxial (CTX) tests, and microscopic scanning tests were carried out to investigate the effects of variable activated carbon contents (namely 0%, 0.25%, 0.75%, 0.50%, 1.00%, and 1.25%, relative to the weight of the sand) on the liquefaction resistance of MICP-treated calcareous sand. The results showed that with the increasing activated carbon, the number of cycles of excess pore water pressure in the cumulative stage of the samples was increased, and the amplitude of axial strain was decreased. As the activated carbon content was increased, the bacterial retention ratio, cyclic strength, and secant modulus of the samples were found to improve considerably. On examination of microscopic scanning images, it was observed that the distribution of excessive activated carbon between the sand particles had resulted in it occupying the bacterial nucleation site and creating an obstacle to the connection between sand particles. The test using 0.75% activated carbon content best enhanced the resistance to liquefaction of calcareous sand. The outcome of this study may in the authors' view prove beneficial in improving the bacterial retention ratio and liquefaction resistance of calcareous sand when it is reinforced by microorganisms. Highlights: The effects of activated carbon on MICP-treated calcareous sand were investigated. A series of bacterial retention tests and cyclic triaxial tests were performed. Microscopic images which revealed the mechanism of activated carbon were obtained. The optimal activated carbon content of liquefaction resistance was found to be 0.75%.